New territories, new perspectives the religious impact of the Louisiana Purchase - Callahan, Richard J., 1967-; NetLibrary, Inc. (Columbia, Mo. : University of Missouri Press, 2008)
"Marking the first study to take the Louisiana Purchase as the focal point for considering development of American religious history, this collection of essays takes up the religious history of the region including perspectives from New Orleans and the Caribbean and the roots of Pentecostalism and Vodou"--Provided by publisher.
Introduction: A reorienting view from the center of the country / by Richard J. Callahan, Jr. -- The religious landscape of the Louisiana Purchase / by Peter W. Williams -- Conflicting destinies : religion, sex, and violence in the Louisiana Purchase / by Amanda Porterfield -- Wide open spaces : the trail of tears, the Lewis and Clark Expedition, and gaps in the national memory / by Michael J. Zogry -- Crossroads, the cosmos, and jazz in the heartland : Oklahoma City's deep deuce and Kansas City's Vine Street / by Douglas Henry Daniels -- The shifting nature of reform envisioned on the Mississippi Steamer : exchanges, masks, and charities in Herman Melville's the confidence-man / by Carole Lynn Stewart -- Mixed-race ecstasy across a single line : the deep south roots of Pentecostal tongue speaking / by Elaine J. Lawless -- Vodou purchase : the Louisiana Purchase in the Caribbean world / by Paul Christopher Johnson -- Spirituality and resistance among African-Creoles / by John Stewart -- New Orleans as an American city : origins, exchanges, materialities, and religion / by Charles H. Long.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: United States -- Church history -- 19th century; Louisiana Purchase; United States -- History -- 1801-1809.; Electronic books